1997
DOI: 10.1243/0957650971537024
|View full text |Cite
|
Sign up to set email alerts
|

Clean coal technologies

Abstract: Power generation in Europe and elsewhere relies heavily on coal as the source of energy and this reliance will increase in the future as other fossil fuels become progressively more expensive. The existing stock of coal-fired power stations mainly use pulverized fuel boilers and present designs based on ultrasupercritical steam cycles are as efficient and as low in SO x and NO x emissions as is possible without incurring excessive additional costs. This paper examines the options for coal-based power generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Nag and Raha (1995) analysed the effect of operating parameters on the performance of a partially gasified combined cycle power plant. McMullan et al (1996) discussed various clean coal technologies and options. De et al (2003a,b) reported some results on energy and exergy analyses of partial gasification pressurized fluidized bed combined cycle power plants.…”
Section: Introductionmentioning
confidence: 99%
“…Nag and Raha (1995) analysed the effect of operating parameters on the performance of a partially gasified combined cycle power plant. McMullan et al (1996) discussed various clean coal technologies and options. De et al (2003a,b) reported some results on energy and exergy analyses of partial gasification pressurized fluidized bed combined cycle power plants.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur dioxide can be removed at the same time, and the integration of the gasifier in a combined cycle (IGCC) has been seen since the 1980s as the cleanest way of generating power from coal. There are several gasifier configurations, but the entrained gasifier has been most developed for this application, notably by Shell and Texaco [7]. Several successful demonstration projects, particularly that of the Shell dry-feed system ( Fig.…”
Section: Gasification Of Coalmentioning
confidence: 99%
“…The integrated gasification combined cycle (IGCC) plant construction technology, used to construct environmentally friendly power generation systems, is gaining popularity [1][2][3][4]. IGCC plants require high-pressure and -temperature operation in order to increase capacity and improve efficiency [5].…”
Section: Introductionmentioning
confidence: 99%